Genetic counselors' perspectives on population‐based screening for BRCA‐related hereditary breast and ovarian cancer and Lynch syndrome. Issue 1 (20th June 2020) - De Simone, Lenika M.; Arjunan, Aishwarya; Vogel Postula, Kristen J.; Maga, Tara; Bucheit, Leslie A.
Abstract: Early identification of those with BRCA‐related Hereditary Breast and Ovarian Cancer Syndrome (HBOC) and Lynch syndrome has the potential for early cancer detection and/or prevention; as such, these conditions are considered Tier 1 genetic conditions by the U.S. Center for Disease Control and Prevention. Given the decreasing cost of genetic testing, population‐based screening (PBS) for such conditions may be the next step toward cancer prevention. This study aimed to understand genetic counselors' perspectives toward offering PBS for the Tier 1 conditions BRCA‐related HBOC and Lynch syndrome. An online survey was distributed to 3, 609 members of the National Society of Genetic Counselors. A total of 367 individuals participated in the study. Fifty percent of respondents felt that PBS for inherited cancer should not be offered; 93.3% felt that the current healthcare system is unprepared for implementation of PBS. However, most respondents agreed that PBS should be implemented within the next 10 years. Attitudes toward offering PBS were associated with respondents' work setting, cancer specialization, and perceived preparedness ( p' s < 0.05). The most commonly reported barriers to the implementation of PBS were shortage of genetic professionals and lack of infrastructure. Data in this study provide evidence that infrastructural barriers and educational gaps of non‐genetic professionals would need to be addressed before successful integration of PBS into the healthcare system.